Systematic review and network meta-analysis of effects of noninvasive brain stimulation on post-stroke cognitive impairment - Wang, Yueying; Xu, Ning; Wang, Runfang; Zai, Weiyi (Frontiers in Neuroscience, 2022)
Objective: To systematically assess the effects of Noninvasive Brain Stimulation (NIBS) on post-stroke cognitive impairment (PSCI) and to compare the efficacy of two different NIBS. Methods: Computer searches of PubMed, Web of Science, Cochrane Library, Embase, China National Knowledge Infrastructure (CNKI), China Science and Technology Journal Database (VIP), Chinese Biomedical literature Service System (SinoMed), and Wanfang Database were conducted using a combination of free words and subject terms. The search was conducted from the database creation date to 16 November 2022. The risk of bias in the included literature was assessed using the Cochrane Risk Assessment Scale. The quality of the included literature was assessed using the physiotherapy evidence database (PEDro) scale. Standard pairwise meta-analysis of study data for each outcome indicator was performed using RevMan 5.4 software. Network meta-analysis was performed using State 14.0 according to the Bayesian framework. Results: A total of 16 studies involving 711 patients were included. Meta-analysis shows NIBS significantly improved montreal cognitive assessment (MoCA) scores (standardized mean difference [SMD] = 0.76, 95% confidence interval (CI) 0.49-1.02, P < 0.05) and mini-mental state examination (MMSE) scores (SMD = 0.79, 95% CI 0.27-1.32, P < 0.05) in patients with PSCI. Transcranial magnetic stimulation (TMS) significantly improved modified barthel index (MBI) scores (SMD = 0.31, 95% CI 0.03-0.59, P < 0.05) in patients with PSCI. The surface under the cumulative ranking curve (SUCRA) of different NIBS in improving MoCA scores were in the order of transcranial direct current stimulation (tDCS) (SUCRA = 92.4%) and TMS (SUCRA = 57.6%). The SUCRA of different NIBS in improving MMSE scores were in the order of tDCS (SUCRA = 78.0%) and TMS (SUCRA = 70.2%). The SUCRA of different NIBS in improving MBI scores were in the order of TMS (SUCRA = 91.7%) and tDCS (SUCRA = 34.3%). Conclusion: The available evidence suggests that NIBS improves cognitive impairment. tDCS appeared more effective than TMS for cognitive function in PSCI patients. However, for activities of daily living ability, TMS may be superior to tDCS.